2022
DOI: 10.1590/1413-81232022275.22742021en
|View full text |Cite
|
Sign up to set email alerts
|

Hospital patient safety at the emergency department - a systematic review

Abstract: Patient safety in health care is the cornerstone of quality in nursing care. It is a duty of nurses and an objective of the health organizations. This article aims to analyze the scientific evidence on the nurses’ perception and opinion on patient safety in the emergency department. Systematic literature review with 3 steps. 1) Primary search at CINHAL and MEDLINE. 2) A broader search, using the same keywords and search terms in the remaining database of the EBSCOHost platform. 3) Search the bibliographic refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similarly, according to a study carried out by Ricklin et al. (2019) and Diz and Lucas (2022), the lack of optimal teamwork is the reason for weakness in the emergency department as to patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, according to a study carried out by Ricklin et al. (2019) and Diz and Lucas (2022), the lack of optimal teamwork is the reason for weakness in the emergency department as to patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study conducted by Habibi Soola et al (2022) in Iran revealed that the patient safety competency of emergency department nurses was primarily related to the structure and leadership of the team and then to psychological safety and experience in patient safety activities. According to a systematic review conducted by Diz and Lucas (2022), the nurses' perceptions indicated that the work environment, teamwork and issues related to the leadership of hierarchical superiors were fundamental factors to improve the quality of care provided and patient safety.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In order to ensure effective communication, the interviews took place in a quiet room in the ED. We employed a semi-structured interview form prepared by the researchers in line with the literature (Alqattan et al,2021;Churruca et al,2021;Diz et al,2022). We proceeded with open-ended questions asked by the first author, who is a trained clinical researcher with a PhD and experience in qualitative designs.…”
Section: Study Samplementioning
confidence: 99%
“…The literature on patient safety indicates that studies with quantitative designs have used measurement tools, and studies with qualitative designs have been few in number (Diz et al, 2022;Churruca et al, 2021). The multidimensional nature of patient safety necessitates the use of qualitative methods (Listiowati et al, 2023;Sarkhosh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%